Abstract Number ‐ 226: Pontine Stroke Presenting as 1.5 Syndrome Evolving to 9 Syndrome over 72 Hours. - Yash Nene; Aravind Reddy; Navreet Kaur; Hesham Masoud (Stroke: Vascular and Interventional Neurology, 2023)
Introduction A 75 year old woman with a past medical history of hypertension developed sudden‐onset vertigo, nausea and vomiting. She did not immediately seek medical care, thinking she was suffering from food poisoning. The following day her symptoms improved however she developed new right sided weakness and gait imbalance, prompting her presentation to the ED. Her neurologic exam noted complete loss of adduction of the right eye and loss of horizontal extraocular movements of the left eye. She also displayed right upper extremity paresis, right upper extremity dysmetria and mild dysarthria. MRI of the brain disclosed acute pontine infarcts in the ventral and dorsal left paramedian regions. Over the next three days, her horizontal gaze palsy improved with some return of adduction of the right eye and horizontal movements of the left eye. However right sided paresis worsened, and in addition, progressed to include complete left facial palsy (lower motor neuron lesion). She was able to be discharged to rehab, placed on Aspirin 81 mg daily and Ezetimibe (due to elevated liver function enzymes) and 30 day Cardiac Event Monitor follow up. Methods Case report and review of literature. Results Due to the combination of multiple cranial nuclei and white matter tracts in the brainstem, ischemia can lead to several clinical manifestations. There are various presenting clinical syndromes, named numerically by structures involved and/or the clinical deficit. One‐and‐a‐half (1.5) syndrome, first reported by Fischer in 1967, is an uncommon entity caused by a lesion (most commonly infarction) in the pontine tegmentum [1]. It consists of complete ipsilateral horizontal gaze palsy (due to involvement of ipsilateral Paramedian Pontine Reticular Formation/Abducens Nucleus and Medial Longitudinal Fasciculus) and loss of adduction of the contralateral eye (due to involvement of the contralateral Medial Longitudinal Fasciculus). Extension of the lesion to the facial nucleus can produce ipsilateral lower motor neuron type facial palsy, leading to an even more uncommon 8.5 syndrome (7 + 1.5), described by Eggenberger in 1998 [2]. When the lesion involves the corticospinal tracts and/or the medial lemniscus, it can lead to contralateral hemiparesis and/or hemisensory deficits; the so called “9 syndrome” first proposed by Rosini et al in 2013 [3]. This rare entity has been reported in only a handful of cases. Conclusions The awareness of complex brainstem neuroanatomy enables precise localization of the clinical deficits. The noted slow progression of the clinical syndrome from 1.5 to 8.5 and finally 9 syndrome over 72 hours in this case highlights the complexity of small vessel brainstem ischemia.